Contagious Ovine Digital Dermatitis: A Novel Bacterial Etiology and Lesion Pathogenesis - Staton, Gareth J.; Angell, Joseph W.; Grove-White, Dai; Clegg, Simon R.; Carter, Stuart D.; Evans, Nicholas J.; Duncan, Jennifer S. (Frontiers in Veterinary Science, 2021)
Contagious ovine digital dermatitis (CODD) is a severe and common infectious foot disease of sheep and a significant animal welfare issue for the sheep industry. The aetiology and pathogenesis of the disease are incompletely understood. In this longitudinal, experimental study, CODD was induced in 18 sheep, and for the first time, the clinical lesion development and associated microbiological changes in CODD affected feet are described over time, resulting in a completely new understanding of the aetiopathogenesis of CODD. The majority of CODD lesions (83.9%) arose from pre-existing interdigital dermatitis (ID) and footrot (FR) lesions. All stages of foot disease were associated with high levels of poly-bacterial colonisation with five pathogens which were detected by qPCR; Treponema medium, Treponema phagedenis, Treponema pedis, Dichelobacter nodosus and Fusobacterium necrophorum. Temporal colonisation patterns showed a trend for early colonisation by Treponema phagedenis, followed by Fusobacterium necrophorum and Dichelobacter nodosus, Treponema medium and then Treponema pedis. Dichelobacter nodosus was present at significantly higher predicted mean log10 concentrations in FR lesions compared to both ID and CODD whilst Treponema species were significantly higher in CODD & FR lesions compared to ID lesions (P < 0.001). Treatment of CODD affected sheep with 2 doses of 10mg/kg amoxicillin resulted in a 91.7% clinical cure rate by 3 weeks post treatment, however a bacteriological cure was not established for all CODD affected feet. The study found that in an infected flock healthy feet, healed CODD feet, and treated CODD feet can be colonised by some or all of the 5 pathogens associated with CODD and therefore could be a source of continued infection in flocks. The study is an experimental study and the findings require validation in field CODD cases. However, it does provide a new understanding of the aetiopathogenesis of CODD, further supportive evidence for the importance of current advice on the control of CODD; which is ensuring optimum flock control of footrot and prompt isolation and effective treatment of clinical cases.